Novel lithium battery nanometer silicon-based negative electrode slurry and preparation method and application thereof

By introducing a protective agent in the preparation of negative electrode slurry of lithium-ion batteries, the problems of poor circulation performance caused by volume expansion of nano-silicon-based negative electrode materials and gas reaction with solvents are solved, and high capacity and good coating performance are achieved.

CN119627052APending Publication Date: 2025-03-14LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311178734.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Nanosilicon-based anode material has poor circulation performance due to volume expansion in lithium-ion batteries, and the increased surface area of ​​the nano-silicon design leads to reaction with solvents, consumes active silicon and produces gases, affecting the coating quality of the electrode sheet.

Method used

Introducing a protective agent in the preparation of the negative electrode slurry, preventing contact of the nano-silicon-based negative electrode material from solvent, avoiding side reactions and gas generation, thereby maintaining high capacity and improving coating processing performance.

Benefits of technology

Effectively maintain the high capacity of nano-silicon-based anode material, avoid gas production during the slurry production, improve coating processing performance, and improve the circulation stability of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627052A_ABST
    Figure CN119627052A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to novel lithium battery nanometer silicon-based negative electrode slurry as well as a preparation method and application thereof. The method comprises the following steps: dissolving a binder in a solvent, and stirring to form homogenate; adding a protective agent into the homogenate, and uniformly mixing; the protective agent comprises one or more of polyethylene glycol (PEG), polyvinylpyrrolidone (PVP), polyvinyl alcohol (PVA), polyacrylic acid (PAA), other polymers containing or generating hydroxyl groups after hydrolysis, and / or a silane coupling agent; and sequentially or simultaneously adding the conductive agent and the nano silicon-based material, continuously mixing, and defoaming to obtain the novel nano silicon-based negative electrode slurry for the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a novel lithium battery nano-silicon-based negative electrode slurry and a preparation method and application thereof. Background Art

[0002] As one of the greatest inventions of the 20th century, lithium-ion batteries are widely used in all aspects of human life due to their advantages such as high specific energy, long cycle life, no memory and low self-discharge rate. Under the background of the dual carbon goals of "carbon peak" and "carbon neutrality", electric vehicles will also be further developed, which is undoubtedly a huge opportunity for lithium-ion batteries.

[0003] Due to the increasing demand for higher energy density, safer and cheaper energy storage devices, the current lithium-ion batteries need to be further developed. As an indispensable part of lithium-ion batteries, the negative electrode greatly affects the performance of lithium-ion batteries.

[0004] At present, the negative electrode materials of lithium-ion batteries are mainly carbon-based and silicon-based materials. Compared with carbon-based negative electrodes, silicon-based negative electrodes have higher theoretical capacity. However, silicon-based negative electrode materials will undergo large volume changes during the lithium ion insertion and extraction process, which leads to poor cycle performance of silicon-based negative electrode batteries. Among the commonly used solutions, the nano-design of negative electrode materials can effectively alleviate the volume expansion problem of silicon-based negative electrodes.

[0005] However, nano-design will bring some negative effects. The reduction of material size will increase the exposed surface area, which will cause more material to react with the solvent during slurry preparation or storage. On the one hand, it will consume active silicon and reduce the specific capacity of the material; on the other hand, it will continue to generate gas, seriously affecting the coating quality of the electrode, or even making it impossible to coat, which seriously restricts the application of existing nano-silicon-based materials. Summary of the invention

[0006] The purpose of the present invention is to provide a novel nano silicon-based negative electrode slurry for lithium batteries and its preparation method and application. By introducing a protective agent in the preparation of the negative electrode slurry, the nano silicon-based negative electrode material can be effectively prevented from contacting with the solvent in the negative electrode slurry, avoiding the occurrence of side reactions that consume active silicon, thereby maintaining the high capacity of the nano silicon-based negative electrode material; at the same time, the negative electrode slurry can be prevented from generating gas during the preparation and storage process, thereby improving the coating and processing performance of the nano silicon-based negative electrode.

[0007] To this end, in a first aspect, an embodiment of the present invention provides a method for preparing a novel lithium battery nano-silicon-based negative electrode slurry, comprising:

[0008] Dissolving the binder in the solvent and stirring to form a homogenous slurry;

[0009] Adding a protective agent to the homogenate for uniform mixing; the protective agent includes: one or more of polyethylene glycol PEG, polyvinyl pyrrolidone PVP, polyvinyl alcohol PVA, polyacrylic acid PAA, other polymers containing or generating hydroxyl groups after hydrolysis, and / or silane coupling agents;

[0010] Then, the conductive agent and the nano silicon-based material are added in sequence or simultaneously and continue to be mixed and degassed to obtain the novel nano silicon-based negative electrode slurry for lithium battery.

[0011] Preferably, the nano-silicon-based negative electrode material includes: nano-silicon material or nano-silicon-carbon composite material; the particle size of the nano-silicon-based negative electrode material is 20 to 100 nm.

[0012] Preferably, the mass ratio of the protective agent to the nano-silicon-based negative electrode material is 1:100 to 20:100.

[0013] Preferably, the solvent includes one or more of deionized water, N,N-dimethylformamide DMF or N-methylpyrrolidone NMP;

[0014] The adhesive includes one or more of polyvinylidene fluoride PVDF, carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR;

[0015] The conductive agent includes one or more of conductive graphite, conductive carbon black, conductive carbon fiber, and graphene.

[0016] Preferably, the stirring speed is 500 rpm to 2000 rpm; the stirring time is 5 to 50 min;

[0017] The mixing rate of the uniform mixing is 500 rpm to 2000 rpm, and the mixing time is 5 to 50 min;

[0018] The mixing rate of the continued mixing is 500 rpm to 2000 rpm, and the mixing time is 5 to 50 min.

[0019] Further preferably, when the conductive agent and the nano-silicon-based material are added in sequence, after the conductive agent is added, the mixture is stirred and mixed at a mixing rate of 500 rpm to 2000 rpm for 5 to 50 min, and after the nano-silicon-based material is added, the mixture is stirred and mixed at a mixing rate of 500 rpm to 2000 rpm for 5 to 50 min;

[0020] When the conductive agent and the nano-silicon-based material are added simultaneously, the mixture is stirred at a mixing rate of 500 rpm to 2000 rpm for 5 to 50 minutes.

[0021] Preferably, the degassing method is vacuum degassing or negative pressure degassing.

[0022] In a second aspect, an embodiment of the present invention provides a novel lithium battery nano-silicon-based negative electrode slurry prepared by the method for preparing the novel lithium battery nano-silicon-based negative electrode slurry described in the first aspect.

[0023] In a third aspect, an embodiment of the present invention provides a lithium battery negative electrode, which is obtained by coating, drying and cutting the novel lithium battery nano-silicon-based negative electrode slurry described in the second aspect.

[0024] In a fourth aspect, an embodiment of the present invention provides a lithium battery, wherein the lithium battery comprises the lithium battery negative electrode described in the third aspect.

[0025] The novel lithium battery nano-silicon-based negative electrode slurry provided in the embodiment of the present invention can effectively prevent the contact between the nano-silicon-based negative electrode material and the solvent in the negative electrode slurry by introducing a protective agent in the preparation of the negative electrode slurry, thereby avoiding the occurrence of side reactions that consume active silicon, thereby maintaining the high capacity of the nano-silicon-based negative electrode material; at the same time, it can avoid the gas generation of the negative electrode slurry during the preparation and storage process, thereby improving the coating and processing performance of the nano-silicon-based negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A flow chart of a preparation process of a novel lithium-ion nano-silicon-based negative electrode provided by an embodiment of the present invention;

[0027] Figure 2 The gas production volume curves of the novel lithium battery nano-silicon-based negative electrode slurries prepared in Examples 1, 2, and 3 of the present invention and the slurry of Comparative Example 1;

[0028] Figure 3 A full battery cycle retention rate curve of the new lithium battery nano-silicon-based negative electrode slurry prepared in Examples 1, 2, and 3 of the present invention and the slurry of Comparative Example 1. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0030] The present invention provides a novel method for preparing nano silicon-based negative electrode slurry for lithium battery, the main steps are as follows: Figure 1 As shown, including:

[0031] Step 110, dissolving the binder in the solvent and stirring to form a homogenous slurry;

[0032] The adhesive includes one or more of polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR);

[0033] The solvent includes one or more of deionized water, N,N-dimethylformamide (DMF) or N-methylpyrrolidone (NMP).

[0034] The stirring speed is 500 rpm to 2000 rpm, for example, 500 rpm, 800 rpm, 1100 rpm, 1400 rpm, 1700 rpm, 2000 rpm. The stirring time is 5 to 50 min, for example, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min. The mixing steps involved in the following steps are not further illustrated, and those skilled in the art can understand how to implement them.

[0035] Step 120, adding a protective agent to the homogenate for uniform mixing;

[0036] The protective agent includes: one or more of polyethylene glycol (PEG), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), polyacrylic acid (PAA), other polymers containing or generating hydroxyl groups after hydrolysis, and / or silane coupling agents; the mass ratio of the protective agent to the nano-silicon-based negative electrode material is 1:100 to 20:100, preferably 8:100 to 15:100.

[0037] The mixing rate for uniform mixing is 500 rpm to 2000 rpm, and the mixing time is 5 to 50 min.

[0038] Step 130, then add the conductive agent and the nano silicon-based material in sequence or simultaneously, continue to mix, and degas, to obtain a novel lithium battery nano silicon-based negative electrode slurry.

[0039] The conductive agent includes one or more of conductive graphite, conductive carbon black, conductive carbon fiber, and graphene;

[0040] Nano silicon-based negative electrode materials include: nano silicon materials or nano silicon-carbon composite materials; the particle size of the nano silicon-based negative electrode material is 20 to 100 nm, preferably 30 to 50 nm. If the particle size of the nano silicon-based negative electrode material is less than 20 nm, the material has a large specific surface area and is easy to absorb moisture and agglomerate, affecting the dispersion effect of the material; if the particle size is greater than 100 nm, it is not conducive to improving the uniformity of mixing.

[0041] When the conductive agent and the nano-silicon-based material are added in sequence, after the conductive agent is added, the mixture is stirred and mixed at a mixing rate of 500 rpm to 2000 rpm for 5 to 50 minutes, and after the nano-silicon-based material is added, the mixture is stirred and mixed at a mixing rate of 500 rpm to 2000 rpm for 5 to 50 minutes;

[0042] When the conductive agent and the nano-silicon-based material are added simultaneously, the mixture is stirred at a mixing rate of 500 rpm to 2000 rpm for 5 to 50 minutes.

[0043] The degassing method is vacuum degassing or negative pressure degassing.

[0044] In the slurry preparation described above, by adding a protective agent, the surface of the nano-silicon-based negative electrode material can be passivated to prevent the silicon-based material from reacting violently with the components in the electrolyte and reduce the generation of gas. This helps to reduce the amount of gas produced during the slurry preparation and storage process; by adding a protective agent, the dispersibility of the nano-silicon-based material in the slurry can be improved, ensuring that the silicon-based particles are evenly dispersed in the slurry, making the surface protection more effective, thereby reducing the generation of gas.

[0045] The new type of lithium battery nano silicon-based negative electrode slurry prepared above can be coated, dried, and cut into pieces to obtain a lithium battery negative electrode, which can be used in lithium batteries. Before coating, the viscosity can be adjusted and a binder can be added as needed. The specific coating, drying, and cutting processes can refer to existing mature processes, so they will not be repeated here.

[0046] The electrode preparation process used in the embodiment of the present invention can effectively improve the gas generation problem during the preparation and storage of the slurry by adding a protective agent during the slurry preparation process, maintain the initial capacity of the active silicon, and the electrode produced using this technology exhibits high cycle stability.

[0047] In order to better understand the technical solution provided by the present invention, the preparation process and performance of the novel nano-silicon-based negative electrode slurry for lithium batteries of the present invention are respectively described below with multiple specific examples.

[0048] Example 1

[0049] This example provides a novel preparation process and performance test of nano-silicon-based negative electrode for lithium batteries, and the specific steps are as follows.

[0050] The preparation of the slurry specifically includes the following steps:

[0051] (1) Add 0.375g CMC to 15g water, with the speed of the dispersion plate at 2000r / min, and disperse for 30min until the gel solution is clear;

[0052] (2) Add 1.42 g of PVA to the glue solution, with the speed of the dispersion disk at 2000 r / min, and disperse for 40 min;

[0053] (3) Add 0.3 g of conductive carbon black SP to the rubber solution, rotate the dispersion disk at 2000 r / min, and disperse for 40 min.

[0054] (4) 14.175 g of active substance nano-silicon was added to the slurry, the dispersion disk speed was 2000 r / min, and the dispersion was carried out for 40 minutes.

[0055] (5) Add appropriate amount of water to adjust the viscosity to 1000-3000 mPa.s. Add 0.375 g of SBR emulsion (solid content 40%) to the slurry, and disperse for 30 minutes at a dispersing disk speed of 1000 r / min. Disperse at a dispersing disk speed of 500 r / min, stir slowly for 30 minutes, and discharge for coating.

[0056] Example 2

[0057] This example provides a novel preparation process and performance test of nano-silicon-based negative electrode for lithium batteries, and the specific steps are as follows.

[0058] The PVA in Example 1 was replaced by PVP, and the remaining steps were the same as those in Example 1.

[0059] Example 3

[0060] This example provides a novel preparation process and performance test of nano-silicon-based negative electrode for lithium batteries, and the specific steps are as follows.

[0061] The PVA in Example 1 was replaced by silane coupling agent KH550, and the remaining steps were the same as in Example 1.

[0062] In order to better illustrate the effects of the embodiments of the present invention, comparative example 1 is compared with embodiment 1, embodiment 2, and embodiment 3.

[0063] Comparative Example 1

[0064] This comparative example directly adopts the traditional negative electrode preparation process without adding a protective agent, and the remaining steps are the same as those in Example 1.

[0065] The gas production of the novel lithium battery nano-silicon-based negative electrode slurries prepared in the above Examples 1-3 and the negative electrode slurry obtained in Comparative Example 1 was tested respectively and assembled into batteries for testing.

[0066] The test method of slurry gas production is as follows:

[0067] Prepare a reaction container and make sure it is clean and free of contamination. Use a weighing device to accurately weigh 10 g of the negative electrode slurry and put it into the reaction container. Seal the reaction container, ensure good sealing performance, and connect a gas collection bag. Place the reaction container in a thermostatic bath and set the temperature to 30 °C. Start the experimental timer and record the start time of the experiment.

[0068] During the experiment, the gas collection channel of the reaction vessel is opened every 5 minutes to collect the generated gas into the gas collection bag, and then the container is sealed. After each gas sample is collected, the gas in the gas collection bag is sent to a gas analysis device such as a gas chromatograph to analyze the composition and concentration of the gas.

[0069] After the 35-minute experiment, the experimental timer was stopped, the end time of the experiment was recorded, and a curve of the gas generation rate versus time was drawn based on the experimental data. Figure 2 According to the experimental results, it can be seen that the slurry of each embodiment of the present invention has a smaller gas production, and the gas production is greatly improved compared with the traditional negative electrode slurry.

[0070] The novel lithium battery nano-silicon-based negative electrode slurry prepared in the above Examples 1-3 and the negative electrode material obtained in Comparative Example 1 are respectively used to prepare and assemble a full battery, and the method specifically includes the following steps:

[0071] Preparation of positive electrode sheet: Nickel-cobalt-manganese ternary material NCM811, polyvinylidene fluoride (PVDF), conductive carbon black (SP) in a mass ratio of 8:1:1 are mixed evenly with N-methylpyrrolidone (NMP) to obtain positive electrode slurry, which is then applied to aluminum foil, rolled and cut, and then welded to the positive aluminum tab to obtain the positive electrode sheet.

[0072] Preparation of negative electrode sheet: coating the obtained negative electrode slurry on copper foil, rolling and cutting it, and welding the negative electrode copper nickel-plated tab to obtain the negative electrode sheet.

[0073] Assemble the full battery: Assemble the above-prepared negative electrode sheet, commercial polyolefin separator, and the above-prepared positive electrode sheet in a staggered stacking manner, and inject 1M LiPF 6 Commercial electrolyte and aluminum-plastic film negative pressure packaging produce a soft-pack full battery.

[0074] Test method: The charge cut-off voltage is 4.5V, the discharge cut-off voltage is 2.75V, and the cycle performance of the full battery is tested at a current rate of 0.1C.

[0075] The cycle retention rates of the full batteries assembled in Examples 1-3 and the comparative examples were tested. Figure 3 As shown in the figure, it can be seen that the cycle performance of the full battery assembled in this embodiment is relatively stable, and there is no adverse situation of rapid capacity decay.

[0076] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a novel lithium battery nano-silicon-based negative electrode slurry, characterized in that: The method comprises: Dissolving the binder in the solvent and stirring to form a homogenous slurry; Adding a protective agent to the homogenate for uniform mixing; the protective agent includes: one or more of polyethylene glycol PEG, polyvinyl pyrrolidone PVP, polyvinyl alcohol PVA, polyacrylic acid PAA, other polymers containing or generating hydroxyl groups after hydrolysis, and / or silane coupling agents; Then, the conductive agent and the nano silicon-based material are added in sequence or simultaneously and continue to be mixed and degassed to obtain the novel nano silicon-based negative electrode slurry for lithium battery.

2. The preparation method according to claim 1, characterized in that: The nano silicon-based negative electrode material comprises: nano silicon material or nano silicon-carbon composite material; the particle size of the nano silicon-based negative electrode material is 20-100 nm.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the protective agent to the nano silicon-based negative electrode material is 1:100 to 20:

100.

4. The preparation method according to claim 1, characterized in that: The solvent includes one or more of deionized water, N,N-dimethylformamide DMF or N-methylpyrrolidone NMP; The adhesive includes one or more of polyvinylidene fluoride PVDF, carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR; The conductive agent includes one or more of conductive graphite, conductive carbon black, conductive carbon fiber, and graphene.

5. The preparation method according to claim 1, characterized in that: The stirring speed is 500 rpm to 2000 rpm; the stirring time is 5 to 50 min; The mixing rate of the uniform mixing is 500 rpm to 2000 rpm, and the mixing time is 5 to 50 min; The mixing rate of the continued mixing is 500 rpm to 2000 rpm, and the mixing time is 5 to 50 min.

6. The preparation method according to claim 5, characterized in that: When the conductive agent and the nano-silicon-based material are added in sequence, after the conductive agent is added, the mixture is stirred and mixed at a mixing rate of 500 rpm to 2000 rpm for 5 to 50 minutes, and after the nano-silicon-based material is added, the mixture is stirred and mixed at a mixing rate of 500 rpm to 2000 rpm for 5 to 50 minutes; When the conductive agent and the nano-silicon-based material are added simultaneously, the mixture is stirred at a mixing rate of 500 rpm to 2000 rpm for 5 to 50 minutes.

7. The preparation method according to claim 1, characterized in that: The degassing method is vacuum degassing or negative pressure degassing.

8. A novel lithium battery nano-silicon-based negative electrode slurry prepared according to the method for preparing a novel lithium battery nano-silicon-based negative electrode slurry according to any one of claims 1 to 7.

9. A lithium battery negative electrode, characterized in that: The lithium battery negative electrode is obtained by coating, drying and cutting the novel lithium battery nano-silicon-based negative electrode slurry as described in claim 8.

10. A lithium battery, characterized in that: The lithium battery comprises the lithium battery negative electrode as described in claim 9 above.